1974
DOI: 10.1088/0029-5515/14/4/010
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear reflexion of laser radiation by a plasma layer in a coherent wave description

Abstract: The paper presents a theoretical analysis of the problem of anomalous reflexion of laser radiation by a plasma due to stimulated scattering by ion-acoustic or electron plasma waves (stimulated Brillouin or Raman scattering). A coherent wave (or well-defined phase) description is used to investigate the case of perpendicular incidence on a plasma layer. The reflexion coefficient as found from the analysis is studied as a function of the power of the laser radiation and of the plasma parameters. The results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We have previously [5], shown that the fraction of the incident laser radiation, which is transmitted through a plasma slab, is equal to 1-Ro-The growth-rate in regions 1 and 2 are…”
Section: P(aw) = -mentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously [5], shown that the fraction of the incident laser radiation, which is transmitted through a plasma slab, is equal to 1-Ro-The growth-rate in regions 1 and 2 are…”
Section: P(aw) = -mentioning
confidence: 98%
“…[l], (see Eq. ( 5)) have previously derived the following expression for the reflection coefficient R o for stimulated scattered radiation in a lossless and homogeneous plasma slab [5]:…”
Section: P(aw) = -mentioning
confidence: 99%
“…(5)) have previously derived the following expression for the reflection coefficient R o for stimulated scattered radiation in a lossless and homogeneous plasma slab [5]: (7) where L o is the length of the plasma slab and L c is the non-linear interaction length. Let R e ff denote the effective value of R.…”
Section: General Theorymentioning
confidence: 99%
“…We have previously [5], shown that the fraction of the incident laser radiation, which is transmitted through a plasma slab, is equal to 1-Ro-The growth-rate in regions 1 and 2 are For large values of R o , i.e. a high-reflexivity situation in the unperturbed state, we obtain large values of r^ 2-This is physically very plausible since in this case there is, loosely speaking, much to gain from the scattering process.…”
Section: General Theorymentioning
confidence: 99%
“…The processes have been studied in computer simulation experiments [6, 71. A theoretical analysis using a well-defined phase description and assuming steady state conditions has been made in [5]. A numerical study of the steady state situation (in the case of Brillouin scattering) has been made in [l] using a random phase description.…”
Section: Introductionmentioning
confidence: 99%